2022
DOI: 10.3390/microorganisms10020278
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Bifidobacteria Important for Infants?

Abstract: The presence of Bifidobacterium species in the maternal vaginal and fecal microbiota is arguably an evolutionary trait that allows these organisms to be primary colonizers of the newborn intestinal tract. Their ability to utilize human milk oligosaccharides fosters their establishment as core health-promoting organisms throughout life. A reduction in their abundance in infants has been shown to increase the prevalence of obesity, diabetes, metabolic disorder, and all-cause mortality later in life. Probiotic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 99 publications
1
32
0
Order By: Relevance
“…The vaginal microbiota was markedly changed, with significantly decreased alpha diversity and abundance of Firmicutes and Lactobacillus , and significantly increased abundance of Proteobacteria ; these changes in microbial composition were also observed in the gut microbiota of neonates. Gestational administration of TMC3115 significantly increased the relative abundance of vaginal Bifidobacterium , which was not found in the gut microbiota of neonates, indicating the TMC3115 might promote the vertical transmission of bifidobacteria from mother’s intestine to vagina as the evolutionary trait of bifidobacteria and the low diversity of vaginal microbiota and the low pH value within vagina ( Wang et al., 2020 ; Stuivenberg et al., 2022 ). These results indicated that gestational TMC3115 treatment could significantly alter the microbiota of the mothers’ vaginas and the pups’ intestines.…”
Section: Discussionmentioning
confidence: 98%
“…The vaginal microbiota was markedly changed, with significantly decreased alpha diversity and abundance of Firmicutes and Lactobacillus , and significantly increased abundance of Proteobacteria ; these changes in microbial composition were also observed in the gut microbiota of neonates. Gestational administration of TMC3115 significantly increased the relative abundance of vaginal Bifidobacterium , which was not found in the gut microbiota of neonates, indicating the TMC3115 might promote the vertical transmission of bifidobacteria from mother’s intestine to vagina as the evolutionary trait of bifidobacteria and the low diversity of vaginal microbiota and the low pH value within vagina ( Wang et al., 2020 ; Stuivenberg et al., 2022 ). These results indicated that gestational TMC3115 treatment could significantly alter the microbiota of the mothers’ vaginas and the pups’ intestines.…”
Section: Discussionmentioning
confidence: 98%
“…Bifidobacteria generate a low-pH environment, produce antimicrobial polysaccharides, and consequently influence the presence of other microbes (53,54). A reduction in Bifidobacteria, related perturbations in interlinked microbes, and disruption of their functions at an early age are associated with immune and metabolic disorders (55)(56)(57). Regarding the Bifidobacteria depletion, the aberrant numbers have been described in CSes and after ATB treatment.…”
Section: Effect Of Breastfeeding On Bifidobacteriamentioning
confidence: 99%
“…LGG, B. breve) and strains unique to pediatrics (B. infantis, L. rheuteri ), however why that is the case does not seem to be evidence-driven but rather historical, general health- and safety-driven. 197 Third, a few studies directly comparing adhesion in infant and adult cell lines are general in referring to barrier function properties or mucus composition, and do not specifically discuss adhesins. Mechanistic studies comparing adhesion factors to age are not available and studies usually consider either infant or adult GIT.…”
Section: Age Related To Probiotic Function and Adhesionmentioning
confidence: 99%